Polysaccharides from Basidiocarps of Cultivating Mushroom Pleurotus ostreatus: Isolation and Structural Characterization - Baeva, Ekaterina; Bleha, Roman; Lavrova, Ekaterina; Sushytskyi, Leonid; Čopíková, Jana; Jablonsky, Ivan; Klouček, Pavel; Synytsya, Andriy (Molecules (Basel, Switzerland), 2019)
Oyster mushrooms are an interesting source of biologically active glucans and other polysaccharides. This work is devoted to the isolation and structural characterization of polysaccharides from basidiocarps of the cultivated oyster mushroom, Pleurotus ostreatus. Five polysaccharidic fractions were obtained by subsequent extraction with cold water, hot water and two subsequent extractions with 1 m sodium hydroxide. Branched partially methoxylated mannogalactan and slightly branched (1→6)-β-d-glucan predominated in cold- and hot-water-soluble fractions, respectively. Alternatively, these polysaccharides were obtained by only hot water extraction and subsequent two-stage chromatographic separation. The alkali-soluble parts originating from the first alkali extraction were then fractionated by dissolution in dimethyl sulfoxide (DMSO). The polysaccharide insoluble in DMSO was identified as linear (1→3)-α-d-glucan, while branched (1→3)(1→6)-β-d-glucans were found to be soluble in DMSO. The second alkaline extract contained the mentioned branched β-d-glucan together with some proteins. Finally, the alkali insoluble part was a cell wall complex of chitin and β-d-glucans.
Keywords: oyster mushrooms; fungální polysacharidy; monosacharidy; chemická frakcionace; Chemical Fractionation; glukany; fytonutrienty; plodnice hub; Glucans; basidiocarps; fractionation; spektrální analýza; Fruiting Bodies, Fungal; glucans; polysaccharides; Phytochemicals; Pleurotus; chromatografie; molekulární struktura; Monosaccharides; Spectrum Analysis; Chromatography; Fungal Polysaccharides; mannogalactan; Molecular Structure